Stereoselective binding of doxazosin enantiomers to plasma proteins from rats, dogs and humans in vitro - Sun Jia-an; De-zhi Kong; Zhen Ya-qin; Li Qing; Zhang Wei; Zhang Jiang-hua; Yin Zhi-wei; Ren Lei-ming (Acta Pharmacologica Sinica; Vol 34, No 12 (December 2013): Acta Pharmacologica Sinica, 2016)
Aim: (±)Doxazosin is a long-lasting inhibitor of α1-adrenoceptors that is widely used to treat benign prostatic hyperplasia and lower urinary tract symptoms. In this study we investigated the stereoselective binding of doxazosin enantiomers to the plasma proteins of rats, dogs and humans in vitro. Methods: Human, dog and rat plasma were prepared. Equilibrium dialysis was used to determine the plasma protein binding of each enantiomer in vitro. Chiral HPLC with fluorescence detection was used to measure the drug concentrations on each side of the dialysis membrane bag. Results: Both the enantiomers were highly bound to the plasma proteins of rats, dogs and humans [(−)doxazosin: 89.4%–94.3%; (+)doxazosin: 90.9%–95.4%]. (+)Doxazosin exhibited significantly higher protein binding capacities than (−)doxazosin in all the three species, and the difference in the bound concentration (Cb) between the two enantiomers was enhanced as their concentrations were increased. Although the percentage of the plasma protein binding in the dog plasma was significantly lower than that in the human plasma at 400 and 800 ng/mL, the corrected percentage of plasma protein binding was dog>human>rat. Conclusion: (−)Doxazosin and (+)doxazosin show stereoselective plasma protein binding with a significant species difference among rats, dogs and humans.